RANCANG BANGUN APLIKASI ABSENSI SISWA SMK NEGERI 2 BALIKPAPAN BERBASIS WEB DENGAN MENGGUNAKAN PHP DAN MARIA DB - Pradana, Danang; Armin, Armin; Ihsan, Ihsan (JIMREK : Jurnal Ilmiah Rekayasa Elektro, 2025)
The number of activities affected by the current pandemic has disrupted community activities, one of which is in the world of education. Several factors have been affected by this pandemic, especially the online learning system and attendance system. Student attendance is one of the important factors in the world of education for the formation of quality and student discipline. In-depth and detailed information about student attendance can determine the quality of student learning. Currently, students at SMK Negeri 2 Balikpapan are still doing attendance manually via google form which is where the google form itself is universal that can be accessed by many people, therefore to maintain attendance data so that it can only be accessed by certain people, an application is made to perform attendance where this application can detect the location of students when doing attendance. The student's location can be obtained by creating a specified location point and adding a distance radius that will serve to validate student attendance information. Making this web application begins with analyzing the needs of the web application to be made, then designing the web display using whimsical, creating a database design, creating PHP program code, and finally implementation. The result of the implementation of the web application that has been made is that this web can run well according to the design that has been made